2009
DOI: 10.1007/s11090-009-9190-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen and Water Vapor on Nitric Oxide Conversion with a Dielectric Barrier Discharge Reactor

Abstract: The effect of O 2 and H 2 O vapor on the Nitric oxide (NO) removal rate, the NO 2 generation rate and the discharge characteristics were investigated using the dielectric barrier discharge (DBD) reactor at 1 atm pressure and at room temperature (20°). The results showed that the O 2 present in the flue gas always hampered the removal of NO and the generation of N 2 O, but that the O 2 could enhance the generation of NO 2 in the NO/N 2 / O 2 mixtures. Furthermore, with the increase of oxygen, the average discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…The maximum peroxynitrite concentration was observed when the energy density reached its peak. Since the dissociation energy level of the O–O bond (4.81 eV) is far less than that of the N–N bond (9.79 eV), [ 55 ] the generation of an oxygen atom is easier than a nitrogen atom via electron impact with the higher energy per area. Likewise, the relatively high oxygen atom concentration is conductive for mode transition according to Kogelschatz and Eliasson's work.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum peroxynitrite concentration was observed when the energy density reached its peak. Since the dissociation energy level of the O–O bond (4.81 eV) is far less than that of the N–N bond (9.79 eV), [ 55 ] the generation of an oxygen atom is easier than a nitrogen atom via electron impact with the higher energy per area. Likewise, the relatively high oxygen atom concentration is conductive for mode transition according to Kogelschatz and Eliasson's work.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the presence of high-water content in the air during ozone generation by dielectric barrier discharge has a serious disadvantage since it results in decomposition of nitrogen and formation of nitrogen radicals. Subsequent chemical reactions may result in the by-production of nitric acid, acting as a caustic and corrosive agent for certain materials [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lot of OH and HO 2 are produced via the reactions ( 5)-( 7) [22]. NO is oxidized to NO 2 , HNO 2 and HNO 3 by OH radical and HO 2 radical via reactions ( 8)- (11) [15,22]. Meanwhile, SO 2 is oxidized to SO 3 by OH radical and HO 2 radical via reactions ( 12)-( 15), and then SO 3 reacts with H 2 O to form H 2 SO 4 [23].…”
Section: Effects Of H 2 O Vapourmentioning
confidence: 99%
“…Yin studied the effect of water vapour and oxygen on NO removal. The experimental results showed that increasing the content of water vapour can significantly reduce the removal efficiency of NO in NO/N 2 /H 2 O gas mixture, O 2 in the flow gas always hampered the removal of NO in NO/ O 2 /N 2 gas mixture [15]. Wang [19].…”
Section: Introductionmentioning
confidence: 99%